GEOCHEMICAL VARIATION WITHIN THE NORTHERN RYUKYU ARC: MAGMA SOURCE COMPOSITIONS AND GEODYNAMIC IMPLICATIONS - Shinjo R.; Woodhead J.D.; Hergt J.M. (My University, 2000)
The major and trace element and Pb–Sr–Nd isotopic compositions of Quaternary mafic lavas from the northern Ryukyu arc provide insights into the nature of the mantle wedge and its tectonic evolution. Beneath the volcanic front in the northern part of the arc, the subducted slab of the Philippine Sea Plate bends sharply and steepens at a depth of ∼80 km. Lavas from the volcanic front have high abundances of large ion lithophile elements and light rare earth elements relative to the high field strength elements, consistent with the result of fluid enrichment processes related to dehydration of the subducting slab. New Pb isotopic data identify two distinct asthenospheric domains in the mantle wedge beneath the south Kyushu and northern Ryukyu arc, which, in a parallel with data from the Lau Basin, appear to reflect mantle with affinities to Indian and Pacific-type mid-ocean ridge basalt (MORB). Indian Ocean MORB-type mantle, contaminated with subducted Ryukyu sediments can account for the variation of lavas erupted on south Kyushu, and probably in the middle Okinawa Trough. In contrast, magmas of the northern Ryukyu volcanic front appear to be derived from sources of Pacific MORB-type mantle contaminated with a sedimentary component. Along-arc variation in the northern Ryukyus reflects increasing involvement of a sedimentary component to the south. Compositions of alkalic basalts from the south Kyushu back-arc resemble intraplate-type basalts erupted in NW Kyushu since ∼12 Ma. We propose that the bending of the subducted slab was either caused by or resulted in lateral migration of asthenospheric mantle, yielding Indian Ocean-type characteristics from a mantle upwelling zone beneath NW Kyushu and the East China Sea. This model also accounts for (1) extensional counter-clockwise crustal rotation (∼4–2 Ma), (2) voluminous andesite volcanism (∼2 Ma), and (3) the recent distinctive felsic magmatism in the south Kyushu region.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная